A dopamine-induced Au hydrogel nanozyme for enhanced biomimetic catalysis. Issue 66 (31st July 2019) - Jiao, Lei; Xu, Weiqing; Yan, Hongye; Wu, Yu; Gu, Wenling; Li, He; Du, Dan; Lin, Yuehe; Zhu, Chengzhou
Abstract : Due to porous nanostructure and polydopamine-induced interfacial electron transfer effects, Au hydrogel nanozyme exhibits enhanced glucose oxidase-like and peroxidase-like activities, with a biomimetic cascade catalysis. Abstract : Au hydrogel with a well-defined nanowire network was rationally designed through one-step dopamine-induced self-assembly. Due to the porous nanostructure along with the polydopamine induced accumulation and interfacial electron transfer effects, the resulting Au hydrogel nanozyme exhibits enhanced glucose oxidase-like activity and peroxidase-like activity, with a biomimetic cascade catalysis.